A systematic review of language and communication intervention research delivered in groups to older adults living in care homes. Issue 1 (28th November 2021) - Davis, Lydia; Botting, Nicola; Cruice, Madeline; Dipper, Lucy
Abstract: Background: The communication skills of older adults living in care homes is an underexplored topic. Ageing can lead to reduced communication ability and activity; and in the care home environment there may also be fewer communication opportunities. This situation is likely to negatively impact well‐being. Previous reviews have found evidence of the effectiveness of behavioural interventions in increasing well‐being, but no systematic review to date has focused specifically on the evidence base for group language and communication interventions in this population. Aims: To identify and evaluate the evidence for behavioural interventions with older adults, delivered in groups in care homes, that specifically included a language or communication activity. To explore the impact of such intervention on the specific domains of language, communication and social interaction. To determine whether behavioural mechanisms of action can be identified. Methods & Procedures: Embase, Medline, Ovid Nursing database, Psych info and CINAHL complete were searched and produced 158 records for screening, of which 22 remained for review. In order to identify and evaluate the quality of the evidence base presented the following research questions were posed: What research has been conducted in this area? What is the methodological quality of the studies identified? How complete is the intervention reporting? How was change measured in the domains of language, communication and social interaction? Is there evidence of efficacy, indicated by statistically significant improvement, in these domains? How did the interventions work? Synthesis tools employed included the PEDro‐P Scale, the TIDieR checklist and the ITAX. Main contribution: A total of 22 studies met the criteria for review. One study used solely language or communication interventions, but the remaining 21 studies used behavioural interventions which incorporated language and communication activities to varying degrees. Studies fell into four broad intervention types: reminiscence or life review; cognitive stimulation; narrative or storytelling; and multi‐modality group communication. The majority of studies were of fair methodological quality, with a moderate level of detail provided in treatment reporting. Statistically significant improvement was reported by authors in all four intervention types and across language, communication and social domains. Social interaction, social support and behavioural skills were the most consistent mechanisms of action in the reviewed behavioural interventions. Conclusions & Implications: Despite limitations in the evidence base, there are important positive signs for the beneficial effects of supporting language and communication in care homes. Blinding of assessors, and the accuracy and accessibility of statistical reporting are important areas to address in order to improve the quality of the evidence base. What this paper adds: Ageing can lead to reduced communication ability and activity, and in the care home setting there may also be fewer communication opportunities. This situation is likely to negatively impact well‐being. Previous reviews have found evidence of the effectiveness of behavioural interventions in increasing well‐being. The communication skills of older adults living in care homes is an underexplored topic. No systematic review to date has focused specifically on the evidence base for group language and communication interventions in this population. This review reveals important positive signs for the beneficial effects of supporting language and communication in care homes. Social interaction, social support, and behavioural skills were the most consistent mechanisms of action in the reviewed behavioural interventions.